The Clue Of The Whistling Bagpipes - Keene Carolyn; Carolyn Keene (New York Carolyn Keene, 1964)
follows Nancy Drew to the Scottish Highlands to solve a missing family heirloom mystery. Amidst threats, she encounters eerie bagpipe noises, a red-bearded stranger, and missing sheep.
Keywords: (1964) is the 41st installment in the Nancy Drew Mystery Stories series by Carolyn Keene. The "conduct of life" depicted in this novel focuses on the proactive, brave, and intellectually curious nature of Nancy Drew, who navigates unfamiliar territory and personal danger to solve crimes; the moral lessons focus on courage, family, and vigilance